Development of Datura metel in different pot sizes (Research, Society and Development, 2021)
Datura metel L. belongs to Solanaceae family and presents medicinal and ornamental potential. The use of D. metel as an ornamental plant is still unexplored, however there is a need to gather more information about this species planting, especially for pot cultivation. This study aimed to verify the effects of different pot sizes in the development of D. metel, in order to enable the use of this species in the potted flower market. The work was conducted in a greenhouse at the Biotechnology Department located at Center of Agricultural Sciences of the Federal University of Paraíba (CCA-UFPB), Areia, PB, Brazil. The experimental design used was completely randomized with 3 treatments (pot sizes: T1 = 0.82 dm3, T2 = 1.55 dm3 e T3 = 3.68 dm3) and 10 replications. The variables analyzed were: plant height, stem diameter, canopy diameter, number of ramifications, leaf length, leaf width, leaf number, flower number, flower length, flower diameter, chrolophyll a e chrolophyll b. The data obtained was submited to analysis of variance and later on clustered based Tukey’s test (5%). All the analyses were made on GENES software. There is variation between treatments for characteristics evaluated. Treatments 2 (1.55dm3) and 3 (3.68dm3) had similar values and the highest mean values for the characteristics of plant height, number of leaves and chlorophyll b. The size of the vase influences the development of the Angel’s trumpet (D. metel). Pot size influences D. metel development. The medium size recipient (1.55 dm3) is recommended for cultivation of D. metel because it presents ideal plant development, such as plant height and number of leaves, for use with ornamental species pots.